Research progress on anti-aging effects and mechanisms of the new ginsenoside Compound K - Zhiqin Fang; Jingyin Zhang; Jianwen Huang; Shuibin Cen (Journal of Dermatologic Science and Cosmetic Technology)
Anti-aging research has become a popular scientific field with the increasing prominence of population aging. Rare ginsenoside Compound K (CK) has attracted widespread attention as an emerging anti-aging active ingredient. The anti-aging effect of ginsenosides is considered to be one of the important roles of ginsenosides, and Compound K, as the main deglycosylated metabolite of ginsenosides, has a comprehensive anti-aging effect as a highly active ingredient obtained by transformation under the action of microbiota. Recent studies have shown that ginsenosides have anti-photo-oxidation, anti-skin aging, free radical scavenging and immunostimulatory effects, which can effectively prevent skin photoaging. With the progress of modern natural medicine extraction technology and the deepening of the research on the anti-skin aging of ginsenosides' high active ingredients, it will promote the development and application of natural product protective skin photoaging preparations. The rare ginsenoside Compound K plays an important role in the improvement of skin health and anti-aging, which is mainly realized by increasing the activity of antioxidant enzymes, inducing the expression of related genes, reducing the content of oxidative damage substances, regulating the immune system, and influencing the expression of cell-cycle regulators and aging genes. A more comprehensive and in-depth study of the molecular mechanism of the anti-aging effect of rare ginsenoside Compound K will be one of the focuses of future research.